Personalized information management by online stores in 4C model: Case study - Anna Kubicka (Foundations of Management, 2016)
The increasing complexity of the business environment, growing knowledge requirements, development of information technologies, and competitiveness implies the need of implementation of information management systems. Moreover, welter of information about online customers, their individual behavior, and their expectations force entrepreneurs to manage information in a personalized way. Monitoring Internet users behavior, creating their profiles (based on data about age, sex, lifestyle, interests, family, work, etc.), and controlling current traffic on the Web site give wide range of possibilities in creating a real model of potential customers preference and using it in online communication. This study concentrates on possibilities of using personalized communication in the information management by online stores in 4C model.
Keywords: 650; personalization; information management; e-commerce; 4C model